ANALISIS KINERJA KEUANGAN PT. MANDOM INDONESIA Tbk PERIODE 2016-2020 DENGAN MENGGUNAKAN ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) - Almeita Gari (Universitas Nias Raya, 2023)
The purpose ofthis study was to calculate the method of Economic Value Added (EVA) and Market Value Added (MVA) in analyzing and knowing the financial performance of PT. Mandom Indonesia Tbk Period 2016-2020. This research is a descriptive qualitative research to analyze the Economic Value Added (EVA) and Market Value Added (MVA) method, namely by using data sourced from PT. Mandom Indonesia Tbk 2016-2020 which is accessed through the website www.idx.co.id. To find out the financial performance of PT. Mandom Indonesia Tbk, it is necessary to analyze the financial statements in the form of income statements and balance sheets and to know the market value of thecompany’s shares. EVA > 0 and from MVA method, the company’s is still able to create Market Value Added or positive value,which is MVA > 0, for fous years consecutively, although one year was in negative value. So it can concluded that the company produces more EVA and increase MVA rather than decrease EVA dan MVA. So that the assessment of financial performance at PT. Mandom Indonesia for the 2016-2020 period was performing well because the company was quite capable and succeeded in increasing economic added and increasing shareholder wealth in the company.